Experience of the application of existing EU directives at the determination of the hazard class of the industrial waste - Stankevych, V.V.; Kostenko, A.I.; Trakhtengerz, G.A. (Environment & Health, 2018)
OBJECTIVE: We substantiated the implementation of modern approaches and techniques on the EU Directives for the determination of the potential hazard of waste. MATERIALS AND METHODS: We analyzed the approaches to the determination of the industrial waste hazard class, carried out a comparison of the results of the studies obtained at the determination of the hazard class using cancelled national standards, directives and regulations of the European Union. RESULTS: The use of directives and regulations of the European Union makes it possible to improve significantly the methodology for the determination of hazard class of the industrial waste. This approach contributes to a more accurate identification of the potential hazard of waste to a human health, taking into account the greater number of factors and ways of the effect of toxic, radioactive and biologically hazardous components of the industrial waste on the human organism in comparison with techniques used in cancelled national standards. CONCLUSIONS: The determination of the potential hazard category of mixtures of waste components by the assessment of inhalation acute toxicity (RT) made it possible to determine the hazard class of waste not only by oral toxicity but taking into account the inhalation route of ingress into organism. The assessment of the aggregate state of waste made it possible to determine the categories of risk and safety when handling them in terms of physical and chemical characteristics which made it possible to assess reasonably all possible manifestations of the potential hazard of waste for the environment and health of the population. The realization of system approach to the determination of the potential hazard of the industrial waste, using standards (EU), is generally aimed to the improvement of regulated handling the waste and improvement of the state of the environment and health of the population.